Evolution of Water Diffusion and Anisotropy in Hyperacute Stroke: Significant Correlation between Fractional Anisotropy and T2 - Ozsunar, Yelda; Grant, P. Ellen; Huisman, Thierry A. G. M.; Schaefer, Pamela W.; Wu, Ona; Sorensen, A. Gregory; Koroshetz, Walter J.; Gonzalez, R. Gilberto (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: We hypothesized that, in acute cerebral ischemic stroke, anisotropic diffusion increases if T2 signal intensity is not substantially elevated and decreases once T2 hyperintensity becomes apparent. Our purpose was to correlate fractional anisotropy (FA) measurements with the clinical time of stroke onset, apparent diffusion coefficients (ADC), and T2 signal intensity.METHODS: Tensor diffusion-weighted images (DWIs) of 25 patients were obtained within 12 hours of symptom onset. Trace DWIs, ADCs, FAs, and echo-planar T2-weighted images (T2WI) were generated. Stroke and contralateral normal volumes of interest (VOIs) were outlined on DWIs and projected onto the inherently coregistered ADC map, FA map, and echo-planar T2WI. Mean signal intensity of the ischemic and contralateral normal VOIs were compared for relatives change in ADC, FA, and signal intensity on T2WIs.RESULTS: A significant negative correlation was observed between FA and T2 signal-intensity change (r = −0.61, P = .00009). A trend of correlation between FA signal intensity and time of onset were found (r = −0.438, P = .025). No significant correlation was found between ADC and FA values (r = −0.302, P = .134). The mean ADC reduction in the ipsilateral ischemic volume was 31% ± 11 compared with the contralateral normal side.CONCLUSION: Change in FA is inversely correlated with T2 signal intensity and, to a lesser extent, the time of onset, but it is not well correlated with ADC values in the acute stage.